دور الاتصال التنموي في تحقیق التنمیة المحلیة المستدامة في مناطق الظل دراسة میدانیة في بلدیة سدراتة - بن قدور بثينة (My University, 2022)
Study Summary: This research, which aims to examine the role of development communication in achieving sustainable local development in the shadow areas of the Sedrata Municipality, addresses the following questions: • Main question: How does development communication contribute to achieving sustainable local development in the Sedrata Municipality? • Sub-questions:  How important is development communication in the municipality's strategy for developing shadow areas?  What are the communication challenges for achieving development goals in the local community?  What is the content of the development communication strategy for developing shadow areas?  What are the obstacles to development communication? This study was conducted on a sample of employees in the Sedrata Municipality. A survey approach was adopted using a questionnaire and an interview tool. After collecting, transcribing, and processing the data using appropriate statistical methods, we reached the following conclusions:  The municipality's communication efforts in the field of development communication are insufficient to achieve sustainable local development goals. Further efforts and programs are required to develop shadow areas.  The inadequate use of communication and media outlets, as well as social media, is underutilized.  The absence of a communications department at the municipal level tasked with planning and implementing communication and media programs and activities.  The absence of communication with local communities and their involvement in the preparation and implementation of development programs, including their environmental, social, and economic dimensions. Finally, we presented a set of proposals that we believe will serve as future research projects for researchers in this field. ------------------------------- ملخص الدراسة: تناولنا في هذا البحث الذي یهدف الى دراسة دور الاتصال التنموي في تحقیق التنمیة المحلیة المستدامة في مناطق الظل ببلدیة سدراتة انطلاقا من التساؤلات التالیة: • التساؤل الرئیسي: كیف یساهم الاتصال التنموي في تحقیق التنمیة المحلیة المستدامة ببلدیة سدراتة. • التساؤلات الفرعیة:  ما مدى أهمیة الاتصال التنموي في استراتیجیة البلدیة لتنمیة مناطق الظل.  ما هي الرهانات الاتصالیة لتحقیق اهداف التنمیة في المجتمع المحلي.  ما مضمون استراتیجیة الاتصال التنموي لتنمیة مناطق الظل.  ما هي العوائق التي تعترض الاتصال التنمو ي. حیث أجریت هذه الدراسة على عینة من الموظفین ببلدیة سدراتة، وتم اعتماد المنهج المسحي باستخدام أداة الاستبیان بالإضافة الى أداة المقابلة. وبعد جمع البیانات وتفریغها ومعالجتها وفق الطرق الإحصائیة المناسبة توصلنا الى النتائج التالیة:  الجهود الاتصالیة التي تبذلها البلدیة في مجال الاتصال التنموي غیر كافیة لتحقیق اهداف التنمیة المحلیة المستدامة وتتطلب المزید من الجهود والبرامج لتنمیة مناطق الظل.  ضعف استخدام وسائل الاتصال والاعلام وكذا وسائل التواصل الاجتماعي بشكل المطلوب.  غیاب جهاز الاتصال على مستوى البلدیة توكل له القیام بعملیات التخطیط وتنفیذ البرامج والأنشطة الاتصالیة والإعلامیة.  غیاب التواصل مع النجب واشراكهم في اعداد وتنفیذ البرامج المرتبطة بالتنمیة ببعدها البیئي والاجتماعي والاقتصادي. وفي الأخیر قدمنا مجموعة من المقترحات التي رأیناها انها ستكون كمشاریع بحث مستقبلیة للباحثین في هذا المجال.
Keywords: التنمية المحلية المستدامة; الاتصال التنمو; ي